Physical activity in adolescents: analysis of the social influence of parents and friends - Luanna Alexandra Cheng; Gerfeson Mendonca; Jose Cazuza de Farias Junior (Elsevier, 2014)
OBJECTIVE: To analyze the association between physical activity and social support from parents and friends on the physical activity level among adolescents. METHODS: Data from 2,361 adolescents (56.6% females; mean age 16.4; SD = 1.2), from public and private high schools were analyzed. The physical activity level of the adolescents, parents, and friends were measured through a questionnaire. Parents' and friends' support and self-efficacy were measured using two previously tested scales. Data analysis was performed usingthe structural equation modeling in IBM(r) SPSS(r) AmosTM 20.0. RESULTS: Physical activity of friends was directly associated with physical activity level of adolescents. Physical activity of the father was associated with their sons, and the physical activity of mother was associated with their daughters. An indirect association was identified between the physical activity of parents and friends with physical activity level of the adolescents, mediated by social support. Social support was directly associated with physical activity in adolescents of both genders and indirectly mediated by self-efficacy. CONCLUSIONS: Parents and friends have a social influence on adolescents' level of physical activity through the mechanism of behavior modeling or through social support, mediated by self-efficacy.